A neofederalist vision of TRIPS : the resilience of the international intellectual property regime - Dinwoodie, Graeme B.; Dreyfuss, Rochelle Cooper, 1947- (Oxford : Oxford University Press, 2012)
The TRIPS Agreement (Agreement on Trade-Related Aspects of Intellectual Property Rights), introduced intellectual property protection into the World Trade Organization's multilateral trading system for the first time. This book examines its interpretation, its impact on the creative environment, and much more.
Includes index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Agreement on Trade-Related Aspects of Intellectual Property Rights (1994); Intellectual property (International law); Foreign trade regulation